Simplifying (x^4y^3)^2
In mathematics, simplifying expressions is a fundamental skill. This article will guide you through the process of simplifying the expression (x^4y^3)^2.
Understanding the Laws of Exponents
To tackle this expression, we need to understand the following laws of exponents:
 Product of powers: x^m * x^n = x^(m+n)
 Power of a product: (x * y)^n = x^n * y^n
 Power of a power: (x^m)^n = x^(m*n)
Simplifying the Expression
Let's break down the simplification stepbystep:

Apply the power of a product rule: (x^4y^3)^2 = (x^4)^2 * (y^3)^2

Apply the power of a power rule: (x^4)^2 * (y^3)^2 = x^(42) * y^(32)

Simplify: x^(42) * y^(32) = x^8y^6
Conclusion
Therefore, the simplified form of (x^4y^3)^2 is x^8y^6. This process demonstrates how to use the laws of exponents to simplify expressions involving powers of variables.